Consolidation characteristics of compacted clayey soils treated with various biomass ashes - Muhammad Abu-Bakr Jamil; Kimitoshi Hayano; Yoshitoshi Mochizuki; Cong Li (Results in Engineering)
The increasing volume of surplus soil generated from excavation works in infrastructure projects such as roads, railroads, and subway facilities poses significant environmental and logistical challenges, particularly in terms of its disposal. Therefore, the development of engineering technologies that promote the effective use of surplus soil has intensified. Among surplus soils, clay is soft and must be treated when used as a backfill or fill material. Cement-based stabilizers are commonly used for soil treatment; however, the production of cement involves high carbon-dioxide emissions, which conflicts with Japan's carbon-neutrality goals. This study investigates the use of alternative stabilizers derived from biomass waste, specifically palm kernel shell ash (PKSA) and rice husk ash (RHA), to treat clayey soils intended for use as a backfill material in road construction. Experiments are conducted to evaluate the compaction and consolidation properties of clayey soils treated with PKSA and RHA. The results indicate that both stabilizers reduced the maximum dry density and increased the optimum water content of the treated soils. PKSA and RHA treatments enhanced compaction control, particularly on the wet side above the optimum water content, thus facilitating the achievement of a high compaction degree of 95 % under high initial water contents. Consolidation test results indicate that treatment with PKSA and RHA increases the consolidation yielding stress and reduces the volume compressibility, and that these effects are more pronounced at higher compaction levels. These results suggest that adding PKSA or RHA can expand the load range that exhibits elastic settlement and may reduce the consolidation settlement. At the same addition rate, PKSA treatment increases the consolidation yielding stress more significantly than RHA treatment. Additionally, PKSA treatment improves the stiffness and reduces the hydraulic conductivity at lower consolidation pressures compared with RHA treatment, thus indicating the greater effect of PKSA. Based on results of scanning electron microscopy, the enhancement in the stiffness and permeability afforded by PKSA is attributed to the formation of needle-like ettringite crystals, which strengthened the soil structure. By contrast, RHA treatment results in densely packed particles, which is attributable to limited hydration reactions caused by low CaO and high SiO₂ contents. Thus, different mechanisms can result in different consolidation parameters of PKSA- and RHA-treated clays. However, both the PKSA- and RHA-treated clays indicate reduced coefficients of volume compressibility and permeability at a compaction degree of 95 %, with a stabilizer-to-clay ratio of up to 15 % by dry mass. Because neither PKSA nor RHA require high addition rates to improve the properties of surplus soft clays, these results suggest that PKSA and RHA can effectively enhance the compaction and consolidation properties of clayey soils. PKSA and RHA treatments are sustainable alternatives to the conventional cement-based treatments and support the environmental goals of construction projects.